2020
DOI: 10.1101/2020.10.13.337782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ubiquitylome of developing cortical neurons

Abstract: TRIM9 and TRIM67 are neuronally-enriched E3 ubiquitin ligases. Both genes are required for neuronal morphological responses to the axon guidance cue netrin-1. For example, our previously published work demonstrated that the actin polymerase VASP and the netrin receptor DCC exhibit TRIM9 dependent ubiquitylation that is lost upon netrin stimulation. Deletion of either gene in the mouse results in subtle neuroanatomical anomalies yet overt deficits in spatial learning and memory. Despite their role in neuronal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It has been suggested that TRIM9 and TRIM67 can act in antagonistic ways, regulating VASP degradation and filopodia extensions (6). However, ubiquitylome analysis in mouse cortical neurons indicated overlapping and non-overlapping targets of TRIM9 and TRIM67, suggesting that both E3 ligases could have redundant and non-redundant functions (20). Our study shows an enrichment of TRIM9 protein levels, physical interaction and colocalization of TRIM9 with TRIM67.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It has been suggested that TRIM9 and TRIM67 can act in antagonistic ways, regulating VASP degradation and filopodia extensions (6). However, ubiquitylome analysis in mouse cortical neurons indicated overlapping and non-overlapping targets of TRIM9 and TRIM67, suggesting that both E3 ligases could have redundant and non-redundant functions (20). Our study shows an enrichment of TRIM9 protein levels, physical interaction and colocalization of TRIM9 with TRIM67.…”
Section: Discussionmentioning
confidence: 54%
“…The TRIM protein family also has E3 ubiquitin ligase activity, and direct ubiquitination targets of TRIM67 has so far been restricted to 80-K-H, such that TRIM67-induced degradation of 80-K-H leads to alteration of Ras signaling in neuroblastoma (10). A recent MS-based study detected potential TRIM67 and TRIM9 ubiquitination targets using mouse primary cortical neurons that need further functional characterization (20). In addition, our MS and co-IP-MS experiments using human glioma cell lines also provide datasets to further identify potential TRIM67 targets and interaction partners.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we have shown that TRIM9 directly interacts and ubiquitinates DCC (Plooster et al ., 2017), as well as the actin polymerase VASP (Menon et al ., 2015; Boyer et al ., 2020). Although our lab has worked to identify new substrates and interacting partners of TRIM9 during axon guidance (Menon et al ., 2020, 2021), there are still dozens of unvalidated candidates waiting to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…, 2020 ). Although our lab has worked to identify new substrates and interacting partners of TRIM9 during axon guidance ( Menon et al. , 2020 , 2021 ), there are still dozens of unvalidated candidates waiting to be explored.…”
Section: Discussionmentioning
confidence: 99%